2022
DOI: 10.7759/cureus.29455
|View full text |Cite
|
Sign up to set email alerts
|

Listerial Meningitis and Brain Abscess With Coexisting COVID-19 Infection in a Young, Immunocompetent Male: A Case Report

Abstract: Listeria monocytogenes (LM) is a gram-positive intracellular pathogen that can cause central nervous system infections such as meningitis, meningoencephalitis, rhombencephalitis, or cerebritis. It rarely causes a brain abscess. Listerial meningitis and brain abscess most commonly occur in immunocompromised individuals, neonates, pregnant females, alcoholics, and the elderly. We present a unique case of a young immunocompetent male who presented with listerial meningitis and brain abscess. Coexisting coronaviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
1
5
0
5
Order By: Relevance
“…To our knowledge, this is the first case of L. monocytogenes bacteremia co‐occurring with COVID‐19 in Japan, similar to that reported from Pakistan 6 . Russell et al.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…To our knowledge, this is the first case of L. monocytogenes bacteremia co‐occurring with COVID‐19 in Japan, similar to that reported from Pakistan 6 . Russell et al.…”
Section: Discussionsupporting
confidence: 80%
“…To our knowledge, this is the first case of L. monocytogenes bacteremia co-occurring with COVID-19 in Japan, similar to that reported from Pakistan. 6 Russell et al reported that bloodstream infections were most frequently caused by Escherichia coli and Staphylococcus aureus in immunocompromised COVID-19 patients, but no case with listeria bacteremia was identified from their multicenter cohort study. 5 L. monocytogenes is an important bacterium in older people and immunosuppressed patients as it can sometimes lead to serious conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although HNIs are prevented by the widespread use of antibiotics for the initial infections, it is still a serious illness that deteriorates over time, especially when it descends into the mediastinum. The mortality rate in this case is 10-40% due to sepsis and organ failure [8,9]. Bacterial colonization within the brain results in a brain abscess which leads to serious consequences.…”
Section: Introductionmentioning
confidence: 88%
“…Focal area of necrosis, with a surrounding membrane within the brain parenchyma, usually resulting from an infectious process or rarely from a traumatic process, known as brain abscess. 1 It may be originated from infections in surrounding area of head and neck or spread from distant organs as hematogenous seedling, known as primary brain abscess. Those that occur after brain injury or brain surgery, these abscesses are labelled secondary brain abscess.…”
Section: Introductionmentioning
confidence: 99%